2008
DOI: 10.1208/s12249-008-9107-z
|View full text |Cite
|
Sign up to set email alerts
|

Control of Transdermal Permeation of Hydrocortisone Acetate from Hydrophilic and Lipophilic Formulations

Abstract: Abstract. The purpose of this research was the preparation of four formulations containing hydrocortisone acetate (HCA) for topical application, including two aqueous systems (hydrophilic microemulsion and aqueous gel) and two systems with dominant hydrophobicity (hydrophobic microemulsion and ointment). The formulations were tested for the release and permeation of HCA across an animal membrane. The release of HCA was found comparable for the four systems. The two microemulsions promote permeation across an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 15 publications
2
44
0
1
Order By: Relevance
“…It was been demonstrated that, at a given concentration, the release is ordinarily faster from the vehicle in which the drug is completely solubilized (Katz & Poulsen, 1972). As demonstrated in previous studies (Raghavan et al, 2001;Fini et al, 2008), MF is insoluble in water and exponentially increases as the amount of glycol is increased. It was shown that in co-solvent mixtures, the solubility of MF was similar for the two glycols, around 3 mg/100 mL.…”
Section: Discussionsupporting
confidence: 71%
“…It was been demonstrated that, at a given concentration, the release is ordinarily faster from the vehicle in which the drug is completely solubilized (Katz & Poulsen, 1972). As demonstrated in previous studies (Raghavan et al, 2001;Fini et al, 2008), MF is insoluble in water and exponentially increases as the amount of glycol is increased. It was shown that in co-solvent mixtures, the solubility of MF was similar for the two glycols, around 3 mg/100 mL.…”
Section: Discussionsupporting
confidence: 71%
“…Our results also demonstrated that the penetration-enhancing effect of ME-hi was significantly higher than ME-lo at 8-12 h postapplication, but affected PGT and ADN delivery differently. A possible explanation for the superiority of ME-hi may rely on differences in the internal structure of the two microemulsions, which leads to different drug release from the formulations and, consequently, different skin penetration (2,11,21). This possibility, however, is not supported by our observation that both microemulsions provided similar release profiles of PGT and ADN.…”
Section: Discussionmentioning
confidence: 59%
“…Microemulsions are emulsions producing a transparent product that has a very small droplet size and does not have tendency to coalesce. A large amount of drug can in fact be incorporated in these formulations, Due to the high solubilising capacity of hydrophobic drugs [10]. …”
Section: Microemulsionmentioning
confidence: 99%